The role of nature in tourism - Latawiec, Michał (Studia Ecologiae et Bioethicae, 2019)
An important reason for doing tourism is the need to contact with nature. Wild nature is threatened by economic and industrial development. The development of tourism enables people to have more contact with nature, but at the same time is the reason for the growing threat to it. There is a strong interaction between nature and tourism. To emphasize this interaction, at the beginning of the article nature will be described as a destination for tourist activities. Then there will be described how the tourism can impact on nature. Finally, I would like to answer the question, how people perceive the nature. The article will emphasise problems and dilemmas arising from the development of tourism and its impact on nature.